314 Audit on Prescription Legibility in an Irish University Teaching Hospital. (16th September 2019) - McCarthy, Christine E; Sebaoui, Salim; Saif, Kiran; Murphy, Elizabeth; Roy, Amrita; Hynes, Jason; Leahy, Aoife; Mohd Asri, Nur Atikah; Quinn, Colin; Peters, Catherine; Lyons, Declan; O'Connor, Margaret
Abstract: Background: Illegible prescribing can lead to medication error and adverse drug reactions. The HSE Standards and Recommended Practices for Healthcare Records Management and the Practice Standards and Guidelines for Nurses for Prescriptive Authority have highlighted criteria which should be adhered to in relation to prescribing. We set out to audit compliance with these standards in relation to legibility of prescriptions in an Irish University Teaching Hospital. Methods: Over a 48 hour period, drug kardexes were reviewed on 14 separate in-patient wards. Legibility was judged by a single assessor on each ward. A drug kardex was deemed legible if all of the following criteria were met: The writing was clear and un-joined, in upper or lower case text. Only approved abbreviations were used. Doses were clear, with zero preceding decimal points, and appropriate measurement units used. In cases where weight dependent medications were prescribed, the patient's weight was clearly documented. The chi squared test was used to determine the significance of the difference in proportions for categorical variables. Results: 285 drug kardexes were reviewed over the 48 hour period. 41% were on surgical wards, 59% were on medical wards. The median patient age was 70 (IQR:55-78), and 56% were male. 48% of drug kardexes were deemed legible. A higher proportion were deemed legible on medical wards compared to surgical wards (68% vs 19% p<0.05). Upper case was used in 13% of kardexes, with similar proportions on medical and surgical wards. Conclusion: Poor legibility of drug kardexes may increase risk of medication errors and adverse drug reactions. We plan to commence targeted prescribing education sessions to highlight the current deficiencies and improve current practice. Changes to kardex layout may also aid legibility. Long term planning for electronic prescribing would also help resolve issues in this area.